Analisis Kelayakan Investasi Alat Sablon Direct Tranfer Film (DTF) (Studi Kasus: UD. Aneka) - Anam, Syahrul Akbariqur; Putri, Erni Puspanantasari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. Aneka is a screen-printing convection business operating with a make-to-order system that still relies on manual printing, resulting in slow production, dependence on skilled labor, and high operational costs. These conditions lead to order delays and reduced production efficiency. Direct Transfer Film (DTF) technology offers a potential solution, as it can accelerate the printing process, reduce unit costs, and improve production capacity and quality. However, adopting DTF requires an initial investment of Rp 30,000,000 with an economic life of five years. Therefore, an investment feasibility analysis was conducted using NPV, IRR, B/C Ratio, and Payback Period methods. The results show an NPV of Rp 10.729.653, an IRR of 36,84%, a B/C Ratio of 1,76, and a Payback Period of 2,15 years, all indicating feasibility. A sensitivity test of ±10–40% on investment costs and raw material costs shows feasibility; at -10% and -20%, sales volume also indicates that the investment remains feasible. Thus, the investment in DTF equipment is declared financially viable